Between season survival of the grasshopper pathogen Melarhizium flavoviride in the Sahel - Thomas, M.B.; Gbongboui, C.; Lomer, C.J. (Informa UK Limited, 1996)
A study is presented showing that the entomopathogenic fungus , Metarhizium avoviride, can persist in fragments of infected grasshopper cadaver and survive the Sahelian dry season. A significant positive relationship was identified between the probability of mortality at the beginning of one season and the density of infected cadaver s present in the habitat at the end of the previous season. Furthermore, survival analysis revealed a steady decline in the mean survival time of grasshoppers exposed to the infected habitats as the density of infected cadaver s used to seed the habitat increased. The consequences of these endings are discussed in the context of the use of M. flavoviride for locust and grasshopper control .